PS 14-71 RENAL ARTERY ANGIOPLASTY FOR RENOVASCULAR HYPERTENSION CAUSED BY TAKAYASU ARTERITIS: TWO-YEAR RESULTS. (September 2016) - Jiang, Xiongjing; Peng, Meng; Ji, Wei; Dong, Hui; Zou, Yubao; Song, Lei; Zhang, Huimin; Wu, Haiying
Abstract : Objective: We aimed to investigate the long-term clinical outcomes of selective stenting versus percutaneous balloon angioplasty (PTA) in hypertensive patients with renal artery stenosis caused by Takayasu arteritis (RASTA). Design and Method: We retrospectively analyzed the data of consecutive152 RASTA patients from Fuwai Hospital between 2005 and 2012. All target lesions of renal arteries were firstly treated by plain PTA. After angioplasty, if flow-limited dissection and/or residual stenosis >50% of diameter on angiogram existed, a selective stenting was then followed to further morphological improvement. Results: The baseline characteristics between PTA (n = 93) and stenting group (n = 59) group were indistinguishable. At two-year follow-up, the rates of normalized, improved, and unaltered hypertension were 27.4%, 63.4% and 12.3 % in PTA group (n = 93) versus 22.4%, 62.1% and 15.5%respectively in stenting group (p = 0.79). Primary patency rate was 90.1% in renal arteries (125 lesions) treated with PTA versus 75.6% in renal arteries (64 lesions) treated with stent placement, (p = 0.008). Female, active stage of the disease requiring glucocorticoid and/or immunosuppressant agents, residual stenosis rate and stenting were significantly associated with the restenosis. In patients with restenosis, renal artery occlusion occurred more in stenting group (8/15), compared with that in PTA group (1/12), p = 0.019. The stenting group underwent more reintervention procedures than PTA group (13/63 versus 8/125, p = 0.003). Conclusions: If PTA alone failed in treating RASTA, selective stenting resulted in similarly effective blood pressure reduction. Stenting also resulted in lower 2-year primary patency rate, higher occlusion rate and higher reintervention rate than those who did not need stenting.